A life-cycle perspective on automotive fuel cells. (1st November 2015) - Simons, Andrew; Bauer, Christian
Highlights: Individual inventories for each fuel cell system component, current and future. Environmental and human health burdens from fuel cell production and end-of-life. Comparison passenger transport in fuel cell and conventional vehicles. Fuel cell can be more critical to overall burdens than hydrogen production. Fuel cell developments require radical but possible changes to reduce burdens. Abstract: The production and end-of-life (EoL) processes for current and future proton exchange membrane fuel cell (PEMFC) systems for road passenger vehicle applications were analysed and quantified in the form of life cycle inventories. The current PEMFC technology is characterised by highly sensitive operating conditions and a high system mass. For each core component of PEMFC there are a range of materials under development and the research aimed to identify those considered realistic for a 2020 future scenario and according to commercial goals of achieving higher performance, increased power density, greater stability and a marked reduction of costs. End-of-life scenarios were developed in consideration of the materials at the focus of recovery efforts. The life cycle impact assessment (LCIA) addressed the production and EoL of the fuel cell systems with inclusion of a sensitivity analysis to assess influences on the results from the key fuel cell parameters. The second part to the LCIA assessed the environmental and human health burdens from passenger transport in a fuel cell vehicle (FCV) with comparison between the 2012 and 2020 fuel cell scenarios and referenced to an internal combustion engine vehicle (ICEV) of Euro5 emission standard. It was seen that whilst the drivetrain (and therefore the fuel cell system) is a major contributor to the emissions in all the indicators shown, the hydrogen use (and therefore the efficiency of the fuel cell system and the method of hydrogen production) can have a far greater influence on the environmental performance. Overall, the results show inconclusive environmental benefits for using FCV instead of modern ICEV: a substantial reduction of Greenhouse Gas (GHG) emissions can only be achieved using hydrogen produced with non-fossil energy resources. However, even such "clean" hydrogen used in FCV will not lead to a reduction of several other environmental burdens from the life cycle perspective within the time frame considered.